Silence and the Word negative theology and incarnation - Davies, Oliver 1956-; Turner, Denys 1942- (Cambridge University Press, 2002)
Negative theology or apophasis - the idea that God is best identified in terms of 'absence', 'otherness', 'difference' - has been influential in modern Christian thought, resonating as it does with secular notions of negation developed in continental philosophy. Apophasis also has a strong intellectual history dating back to the early Church Fathers. Silence and the Word both studies the history of apophasis and examines its relationship with contemporary secular philosophy. Leading Christian thinkers explore in their own way the extent to which the concept of the apophatic illumines some of the deepest doctrinal structures of Christian faith, and of Christian self-understanding both in terms of its historical and contemporary situatedness, showing how a dimension of negativity has characterised not only traditional mysticism but most forms of Christian thought over the years